Research on the Forced Vibration Characteristic of the Dual Mode Multistage Gear Transmission based on the Objective Parameter Optimization - Xiaoci Huang (Jixie chuandong)
In order to analyze the cause and influence factors of the torsional vibration of the dual mode multistage gear transmission， a hybrid electric vehicle dynamic model is established based on SIMPACK. By means of imposed excitation on the dynamics model and set output channel on it， a simulation system for torsional vibration is constructed. The vibration mode of transmission is analyzed as a torsional vibration simulation system， and is validated by the results of theoretical calculation and experimentation， which verified the effectiveness of the established simulation system. On this basis， some objective parameters， such as stiffness and damping of torsional damper， are analyzed for the effect of dampen vibration. The result shows that it has a good effect on the attenuation of torsional vibration in certain frequency through adjustments to characteristic parameters of torsional damper in a proper range.